Education Through The Abat Method In Improving Teenagers Awareness of HIV/AIDS Risks At YPKP Sentani Vocational School - Handayani, Endah; Harlinda Widia Putri; Susi Lestari; Eftyaningrum Dwi Wahyu Astutik (Journal of Community Engagement in Health, 2025)
Reproductive health issues frequently encountered during adolescence include premarital pregnancy, promiscuity, and other issues with all their consequences, which are among the causes of adolescents' risk of exposure to Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS). Data from the Sentani City Health Center from January to August 2022 showed that 220 people were infected with HIV/AIDS. At the Sentani City Health Center, HIV/AIDS cases were handled through screening to determine the number of people infected with the virus each month. The method of implementing the activities was carried out through an approach, namely analyzing the conditions of the target area, followed by identifying problems, planning interventions and implementing implementation in addressing the planned problems by carrying out activities in the form of providing education. The promotional media used in this activity was the ABAT method on HIV/AIDS. ABAT stands for “Aku Bangga Aku Tahu” which in English means “I Am Proud I Know”. Part of a campaign or approach under the Information, Education, and Communication, framework, specifically targeting young people (ages around 15-24) to increase their awareness and knowledge about HIV/AIDS. The results of this community service activity showed that respondents who scored well on the pre-test were 76%, increasing to 96% of respondents on the post-test score results. So it can be concluded that there was an increase in respondent scores between the pre-test and post-test with educational interventions through the ABAT method on HIV/AIDS prevention likes Comprehensive Sexual and Reproductive Health Education, Promotion of Safe Sexual Practices and Anti-Stigma Campaigns.